Current practice of anticholinergic use in conjunction with antipsychotic agents at Helen Joseph Hospital Psychiatric Outpatients - Heydenrych, Xandri (My University, 2018)
Antipsychotic agents are used in the management of psychiatric disorders. Anticholinergic agents are co-prescribed for neuroleptic-induced side effects.
A Research report submitted to the faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, Johannesburg, 2018